Observation of the Out‐of‐Plane Polarized Spin Current from CVD Grown WTe2. Issue 8 (19th June 2021) - Shi, Shuyuan; Li, Jie; Hsu, Chuang‐Han; Lee, Kyusup; Wang, Yi; Yang, Li; Wang, Junyong; Wang, Qisheng; Wu, Hao; Zhang, Wenfeng; Eda, Goki; Liang, Gengchiau; et al.
Abstract: Weyl semimetal Td‐phase WTe2 possesses the spin‐resolved band structure with strong spin–orbit coupling, holding promises as a useful spin source material. The noncentrosymmetric crystalline structure of Td‐WTe2 endows the generation of the out‐of‐plane polarized spin, which is of great interest in magnetic memory applications. Previously, WTe2 was explored in spin devices based on mechanically exfoliated single crystal flakes with a size of micrometers. For practical spintronics applications, it is highly desirable to implement wafer‐scale thin films. In this work, centimeter‐scale chemical vapor deposition (CVD) grown Td‐WTe2 thin films are used and the spin current generation is studied by the spin torque ferromagnetic resonance (ST‐FMR) technique. The in‐plane and out‐of‐plane spin conductivities of 7.36 × 10 3 ( ℏ / 2 e ) (Ωm) –1 and 1.76 × 10 3 ( ℏ / 2 e ) (Ωm) –1, respectively, are found in CVD‐growth 5 nm‐WTe2 . The current‐induced magnetization switching in WTe2 /NiFe is demonstrated at room temperature in the domain wall motion regime, which may invigorate potential spintronic device innovations based on Weyl semimetals. Abstract : Weyl semimetal WTe2 holds promise as a useful spin current generator, which was previously explored in mechanically exfoliated flakes. Here, centimeter‐scale chemical vapor deposition WTe2 thin films are used and both the in‐pane and out‐of‐plane spin currents are found. The results are highly desirable for practical applications and provide an impetus for magnetization switching devices using Weyl semimetals.